Knowledge Ottoman Turkish Medicine : From Methods of Immunization Traditional to Pioneer World Vaccine - Rafid Sugandi (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2024)
This research explores the history of immunization "vaccination" which was known as the variation method during the Ottoman Turkish period. The method used is the historical method, with the stages of source collection, source criticism, interpretation and writing. Data were collected from conventional and non-conventional libraries (internet), sources collected in the form of books, journal articles, website articles and others printed or from the internet that support this research. Furthermore, the facts obtained are narrated diachronically so that the facts described are chronological. The results of this study show that the development of vaccines that is happening now is a great contribution from Ottoman Turkey. The history of vaccination was started by the Ottoman Turkish government, Ottoman (Ottoman Turkish) physicians created and developed the variolation (inoculation) method, a traditional vaccine method by taming and using viruses (germs) applied to human skin that had previously been scratched. In this way, the virus injected into the human body (smallpox sufferers or non-smallpox sufferers) will experience illness and during the illness the immune process is formed so that the patient will get immunity (antibody). The success of vaccination from Ottoman Turkey has spread to Europe which saved many human lives and eradicated smallpox, especially England which was brought by Lady Mary Montagu, traders, sailors, ambassadors and others who learned the variolation method from Ottoman Turkey.